Understanding the Role of Shatavari (Asparagus racemosus) in Enhancing Female Fertility a Traditional Perspective (International Journal of Ayurveda and Pharma Research, 2025)
Shatavari (Asparagus racemosus) is a prominent medicinal herb utilized in Ayurveda, primarily recognized for its benefits in supporting female reproductive health. This review investigates its potential to enhance female fertility by examining its phytochemical makeup, pharmacological properties, and therapeutic uses. It discusses both traditional and contemporary viewpoints regarding Shatavari's effectiveness in improving reproductive health, supported by various scientific studies. Additionally, the review highlights Shatavari’s adaptogenic qualities, its function in managing polycystic ovarian syndrome (PCOS), and its effects on mental and emotional health concerning fertility. The underlying mechanisms through which Shatavari works- such as hormonal regulation, antioxidant properties, and immune system support- are also analyzed. Moreover, the clinical applications of Shatavari in treating menstrual irregularities, pregnancy-related issues, lactation, and menopause symptoms are considered. Although current findings suggest significant benefits of Shatavari in promoting fertility, further extensive clinical trials are necessary to determine its efficacy, optimal dosage, and safety. The herb's cultural importance in traditional medicine, along with its increasing recognition in integrative healthcare systems, underscores the urgency for continued research. This review aims to furnish a thorough understanding of Shatavari's significance in female reproductive health and its implications for future research endeavors and clinical applications.